SIFAT FISIS DAN MEKANIS KOMPOSIT SERAT LIMBAH PATI ONGGOK SANDWICH DENGAN CORE SERAT ACAK DARI BAHAN LIMBAH SEKAM PADI DENGAN MATRIK RESI - Ngafwan, Ngafwan (Universitas Muhammadiyah Surakarta, 2007)
Nature composite from skin rice fibre and palm sago fibre have different mechanical and physycs properties characteristic , that have done from result of our researh before. Therefore there is many research that can composse the properties of materials above. The methode of compossing two fiber use poliester that have 20%, 30%, and 40% volume fraction of that matrice, compossing with sandwich layer. Caracterizing properties testing used are thermal conductivity test, and bending test. The result are, at high thermal condition the conductivity was decrease for all above materials. The decreasing of conductivity of this sandwich compsite is more significant. The sandwich composite more tough than skin rice fibre composite. The resume is the mechanical properties ( bending toughness) more less significant of the thermal conductivity that more better.